Pentingnya Pemberian ASI Eksklusif dan Cara Menyusui yang Baik dan Benar di RW 07 Desa Babakan Kecamatan Ciseeng Kabupaten Bogor 2025 - Fitria Lestari; Khoirunnisa Khoirunnisa; Milda Maulida; Meiki Shindi; Nur Holifah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
One of the influences on the success of exclusive breastfeeding is the role of midwives, namely providing counseling on preparation for exclusive breastfeeding, Early Breastfeeding Initiation (IMD) during childbirth, how to do breast care during pregnancy and the benefits of exclusive breastfeeding. The purpose of Community Midwifery Intervention Practice is to educate in order to increase public awareness of the importance of exclusive breastfeeding and good and correct breastfeeding methods. The method of activity is through counseling by providing material directly using supporting media power points and booklets given to pregnant women, breastfeeding mothers, and grandmothers who take care of their grandchildren and discussions about the importance of exclusive breastfeeding and good and correct breastfeeding methods and there is an evaluation through pre and post-test with 10 questions. The results of 30 respondents can be seen from the pre-test with good knowledge of 9 people (30%) and after the counseling there was an increase in the results of the post-test with good knowledge of 30 people (100%), indicating an increase of 70%. with ρ value = 0.000 (ρ <0.05) meaning that there is an influence on the Importance of Exclusive Breastfeeding and Good and Correct Breastfeeding Methods and a t value of 8.226. In conclusion, there is an influence on increasing knowledge of the Importance of Exclusive Breastfeeding and Good and Correct Breastfeeding Methods after counseling at Posyandu Mawar Indah 02.